Comprehensive Analysis for Long-Term Hydrological Simulation by Deep Learning Techniques and Remote Sensing - Xu, Chaowei; Wang, Yizhen; Fu, Hao; Yang, Jiashuai (Frontiers in Earth Science, 2022)
Hydrological simulation plays a very important role in understanding the hydrological processes, and is of great significance to flood forecasting and optimal allocation of water resources in the watershed. The development of deep learning techniques has brought new opportunities and methods for long-term hydrological simulation research at watershed scale. Different from traditional hydrological models, the application of deep learning techniques in the hydrological field has greatly promoted the development trend of runoff prediction and provide a new paradigm for hydrological simulation. In this paper, a CNN-LSTM model based on convolutional neural network (CNN) and long short-term memory (LSTM) network and a CNN-GRU model based on CNN and gated recurrent unit (GRN) are constructed to study watershed hydrological. To compare the performance of deep learning techniques and hydrological model, we also constructed the distributed hydrological model: Soil and Water Assessment Tool (SWAT) model based on remote sensing data. These models were applied to Xixian basin and the promising results had been achieved, which verified the rationality of the method with the majority of percent bias error (PBE) values ranging between 3.17 and 13.48, Nash-Sutcliffe efficiency (NSE) values ranging between 0.63 and 0.91, and Kling-Gupta efficiency (KGE) values ranging between 0.70 and 0.90 on monthly scale. The results demonstrated their strong ability to learn complex hydrological processes. Results also indicated that the proposed deep learning models could provide certain decision support for the water environment management at watershed scale, which was of great significance to improve the hydrological disaster prediction ability and was conducive to the sustainable development of water resources.